(3GdQSGdI GdecjIs - (3bWH GdOjf YHO Gddg Hf eMeO Hf Gjef GdGUagjQjs ((3YeQ Hf CMeO Hf YHO GdQMje Hf jMji GdGfUGQi s)
(3ChdgG (B:s
(3GdMeO ddg GdYXje TCfg Gdbhi SdWGfg CeG HYO abO CdaJ gPG GdJCdja ai ecI TQagG Gddg JYGdi Ke GSJOQcJg HeOjfI OeTb hROJ ajg ahGFO s
(3BNQgG (B:s
(3Yf YGFTI Yf fHjc Yf LHQjd Efc bdJ Cfi dCSJMi Cf CYPH ef TGH ai GdGSdGe TjHg bGd Gddg YR hLd UOb eYeQ UOb GdfHi UOb LHQjd hCfG GdUGOb EPgH abO YahJ Yfc hUdi Gddg Ydi SjOfG eMeO hYdi Gdg hUMHg hSde s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdKGefs
(3GdJhKjbGJ GdeQLYjI (B:s
(3cTa GdXfhf dMGLi NdjaI(B: (3L (B1 - (3U (B893s
(3JHUQGJ GdCUd (B:s
Keywords: (3GdJUha hGdBOGH GdTQYjIs